On Variable Majority Rule and Kramer's Dynamic Competitive Process - Blair, Douglas H. (Review of Economic Studies, 1979)
Journal Article On Variable Majority Rule and Kramer's Dynamic Competitive Process Get access Douglas H. Blair Douglas H. Blair University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 4, October 1979, Pages 667–673, https://doi.org/10.2307/2297034 Published: 01 October 1979 Article history Received: 01 December 1975 Accepted: 01 November 1978 Published: 01 October 1979